2016
DOI: 10.1007/s11356-016-6587-3
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in sediments, soils, and aquatic plants from a secondary anabranch of the three gorges reservoir region, China

Abstract: We investigated the occurrence of cadmium (Cd), copper (Cu), chromium (Cr), nickel (Ni), lead (Pb), Znic (Zn), iron (Fe), manganese (Mn), and magnesium (Mg) in sediments, as well as in related soils and aquatic plants in the Liangtan River, a typical secondary anabranch of the Yangtze River in the Three Gorges Reservoir Region (TGRR) of China. We found that sediments accumulated more metals than soils and aquatic plants. Concentrations of the nine metals in sediments and soils followed the same sequence, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 31 publications
5
6
0
Order By: Relevance
“…In general, in most of the studies presented, the range of nickel content in aquatic plants is similar to that recorded in this study and reaches a maximum threshold at 24.67 mgNi•kg −1 [32,33,[37][38][39]41,43,45,46,49,51,52,54].…”
Section: Nickelsupporting
confidence: 88%
See 2 more Smart Citations
“…In general, in most of the studies presented, the range of nickel content in aquatic plants is similar to that recorded in this study and reaches a maximum threshold at 24.67 mgNi•kg −1 [32,33,[37][38][39]41,43,45,46,49,51,52,54].…”
Section: Nickelsupporting
confidence: 88%
“…Cadmium bioaccumulation factor with respect to sediment (BCF B = 0.0209-41.07) was lower than with respect to water (BCF W = 5.35-18,155.50) (Table 5). In studies on the Strzegomka, Nysa Szalona and Bystrzyca Rivers conducted in previous years, the cadmium content in plants was similar to the results obtained in this study, with levels reaching a maximum of 8.80 mgCd•kg −1 [2,4,5,16,31,32,35,[37][38][39][40][41][42][43][45][46][47][48][49]51,52]. This indicates a persistently stable level of cadmium in the environment and relatively unchanged water chemistry conditions.…”
Section: Cadmiumsupporting
confidence: 86%
See 1 more Smart Citation
“…Based on the Pb isotope composition, Bing et al [22] concluded that Pb in the sediments of TGR mainly originated from industrial discharge, domestic sewage, mining, smelting, and the shipping industry. However, Cd is an identification element of agricultural activities, i.e., the application of pesticides and fertilizers [25,46]. Liu et al [47] stated that Cd is found predominantly in phosphate fertilizers as an impurity of phosphate rocks; and the amount of pesticides and fertilizers used in the TGR were 601.8 tons of 135,000 tons, respectively, in 2015 [13].…”
Section: Source Identificationmentioning
confidence: 99%
“…The contamination of heavy metals in rivers or lakes has drawn increasing attention [ 1 ], as heavy metals have characteristics of potential toxicity, persistence, and non-biodegradation which pose potential risks on aquatic ecosystems and human health [ 2 , 3 , 4 ]. In an aquatic ecosystem, sediment is an important component, acting as a major sink for heavy metals due to their great tendency of adsorbing onto solid phases [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%